2014
DOI: 10.1534/g3.114.013292
|View full text |Cite
|
Sign up to set email alerts
|

An X-Linked Sex Ratio Distorter in Drosophila simulans That Kills or Incapacitates Both Noncarrier Sperm and Sons

Abstract: Genomic conflict occurs when a genomic component gains a reproductive advantage at the expense of the organism as a whole. X-linked segregation distorters kill or incapacitate Y-bearing sperm, thereby gaining a transmission advantage but also reducing male fertility and generating a female-biased sex ratio. When some damaged, Y-bearing sperm survive and fertilize eggs, then the segregation distortion phenotype could be expanded by harming or killing sons in the next generation. X-linked son-killers are predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…However, based on our phylogeny it is most parsimonious that the sensitive lineage (Cluster I) corresponds to a secondary loss of resistance to Paris SR. Consistently, previous work suggested that the Y chromosome of D. sechellia is resistant to the Paris drivers (Tao et al 2007; Rice 2014).…”
Section: Discussionsupporting
confidence: 85%
“…However, based on our phylogeny it is most parsimonious that the sensitive lineage (Cluster I) corresponds to a secondary loss of resistance to Paris SR. Consistently, previous work suggested that the Y chromosome of D. sechellia is resistant to the Paris drivers (Tao et al 2007; Rice 2014).…”
Section: Discussionsupporting
confidence: 85%
“…[19][20][21][22] Biased sex ratios have also been reported. [23][24][25][26][27][28][29] These exceptions arise despite strong selective pressures that strive to maintain normal segregation 2 and sex ratios 30,31 Based on haploid effects in gametes, one allele is preferentially transmitted to offspring at the expense of other alleles. TRD is usually the property of one sex, driving allelic preference regardless of the genetics of the mating partner.…”
Section: Introductionmentioning
confidence: 99%